EMODIN DOWNREGULATES CELL PROLIFERATION MARKERS DURING DMBA INDUCED ORAL CARCINOGENESIS IN GOLDEN SYRIAN HAMSTERS - Manimaran, Asokan; Buddhan, Rajamanickam; Manoharan, Shanmugam (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Cell-cycle disruption is the major characteristic features of neoplastic transformation and the status of cell-cycleregulators can thus be utilized to assess the prognostic significance in patients with cancer. The PCNA, cyclin D1, CDK4, CDK6and survivin expression in the buccal mucosa was utilized to evaluate the Emodin efficacy on abnormal cell proliferation during7,12-dimethylbenz(a)anthracene (DMBA) induced oral carcinogenesis in golden Syrian hamsters.Materials and methods: Topical application of DMBA, three times a week for 14 weeks, on the hamsters' buccal pouchesdeveloped well differentiated squamous cell carcinoma.Results: Cyclin D1 and PCNA over-expression and up-regulation of CDK4, CDK6 and survivin were noticed in the buccalmucosa of hamsters treated with DMBA alone. Emodin administration (50mg/kg b.w) orally to hamsters treated with DMBAdown-regulated the expression of cell proliferation markers in the buccal mucosa.Conclusions: The anti-cell proliferative role of Emodin is owing to its modulating efficacy on cell-cycle markers towards thetumor suppression during DMBA induced oral carcinogenesis.